Effects of Metformin on the Bioactivity and Osseointegration of Dental Implants - Dr Usman Manzoor Warraich; Zainab khan; Dr Muhammad Tariq Fayyaz; Dr. Asad Farooq; Dr. Umar farooq khan; Dr. Ammar Abdullah Malik (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Metformin is known to benefit bone remodeling and increase osteoblast activity, thus it may have some medicinal value in dentistry. This study aimed to analyze its influence on the osseointegration of dental implants. Objective: To assess the impact of metformin in boosting the bioactivity, osseointegration, and efficacy of dental implants. Methods: This study was a randomized, double blinded, placebo controlled trial conducted on 100 patients aged 25-60 years scheduled for dental implants. Patients received either metabolic adjunct (500mg, twice daily) or placebo for 12 weeks. Assessment of the implants stability, bone density, and activity if osteoprogenitor cells was done at the baseline, 6 weeks, and 12 weeks after implant placement. Results: Patients in the Metformin group showed improved stability of the implants, osteoblast activity, and bone density as compared to the control group. Bone formation and maturation around the implants was also better in patients on Metformin. Conclusion: Metformin increases the bioactivity and osseointegration of the dental implants therefore may be considered an adjunctive therapy for improving the success rate of implants and bone healing in dental patients.